2018
DOI: 10.1111/imcb.12007
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccination drives accumulation and effector function of innate lymphoid cells in murine lungs

Abstract: The tuberculosis (TB) vaccine bacille Calmette-Guérin (BCG) prevents disseminated childhood TB; however, it fails to protect against the more prevalent pulmonary TB. Limited understanding of the immune response to Mycobacterium tuberculosis, the causative agent of TB, has hindered development of improved vaccines. Although memory CD4 T cells are considered the main mediators of protection against TB, recent studies suggest there are other key subsets that contribute to antimycobacterial immunity. To that end, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 50 publications
3
40
0
1
Order By: Relevance
“…This effect was even more pronounced when IL‐10 signaling was inhibited by anti‐IL‐10R treatment. A recent study further identified an accumulation of ILC1 (Lin − CD90.2 + CD127 + IL‐17RB − IL‐23R − NKp46 + ), ILC2 (Lin − CD90.2 + CD127 + IL‐17RB + ) and ILC3 (Lin − CD90.2 + CD127 + IL‐17RB − IL‐23R + NKp46 +/− ) in the lungs along with enhanced IFN‐γ production after different routes of BCG vaccination . A more thorough analysis of the ILC subsets, including characterization using transcription factors would help to gain clear evidence for the involvement of ILCs in M. tuberculosis infection.…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 97%
“…This effect was even more pronounced when IL‐10 signaling was inhibited by anti‐IL‐10R treatment. A recent study further identified an accumulation of ILC1 (Lin − CD90.2 + CD127 + IL‐17RB − IL‐23R − NKp46 + ), ILC2 (Lin − CD90.2 + CD127 + IL‐17RB + ) and ILC3 (Lin − CD90.2 + CD127 + IL‐17RB − IL‐23R + NKp46 +/− ) in the lungs along with enhanced IFN‐γ production after different routes of BCG vaccination . A more thorough analysis of the ILC subsets, including characterization using transcription factors would help to gain clear evidence for the involvement of ILCs in M. tuberculosis infection.…”
Section: Role Of Ilcs In Lung Infection and Ilc Immunitymentioning
confidence: 97%
“…Steigler et al . BCG vaccination drives accumulation and effector function of innate lymphoid cells in murine lungs Barnes & Cyster.…”
mentioning
confidence: 99%
“…Another key topic covered in our top 10 publications is the identification and characterization of innate and innate‐like lymphocytes including innate lymphoid cells (ILC), mucosal‐associated invariant T (MAIT) cells, and natural killer T (NKT) cells . The study by Steigler et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations